PERSONALITY DEVELOPMENT TRAINING FOR HIGH SCHOOL STUDENTS EXPERIENCING THE GANG MOTOR PROBLEMS IN MEDAN - Rahmi Lubis (Jurnal Pengabdian Sriwijaya, 2014)
The rise of motorcycle gang action has caused casualties and material losses. The government has tried to redress through the legal process and prevention through extension activities. Faculty of Psychology, University of Medan Area as an institution of higher education felt called to assist the government in handling this issue, through a program of community service personality development training for high school students who allegedly have links with the action alley bike in the city of Medan. This event was organized by the coaches who have experience in the field of the high school students, vocational NP, and BS Field High School. Training was given for 3 days for each school includes self knowledge, safe driving and entrepreneurship. With a total of 77 participants obtained results that safety riding training modules provide a significant effect on the change in students' attitudes toward safe driving at high school students (t = 7.694, p <0.05). For SMA Nusa Penida obtained a significant increase in knowledge of safe driving (t = 2.059, p <0.05) and highly significant on entrepreneurial knowledge (t = 0.797 p <0.01), but the student has not shown any significant change in attitude related these aspects. While the high school students of BS just show increased knowledge of self knowledge training material (t = 1.134 p <0.05) but self knowledge of the participants themselves have not shown marked improvement.